The efficiency of the Polish zloty exchange rate market: The uncovered interest parity and fractal analysis approaches - Katarzyna Czech; Łukasz Pietrych (Risks, 2021)
The study of the effectiveness of the currency market is one of the most important research problems in the field of finance. The paper aims to assess the efficiency of the Polish zloty exchange rate market. We test the market efficiency by applying two independent approaches, one based on the Uncovered Interest Parity theory, and another based on the fractal analysis of exchange rates series. The research results show that the Uncovered Interest Parity holds only on the USD/PLN market. For EUR/PLN, JPY/PLN, CHF/PLN, MXN/PLN and TRY/PLN, the Uncovered Interest Parity hypothesis is rejected and implies the existence of the forward premium anomaly and market inefficiency. The estimated Hurst coefficient provides insight into the long-range dependence of exchange rates. The MXN/PLN, TRY/PLN and EUR/PLN exchange rates exhibit anti-persistent behaviours suggesting mean-reverting characteristics. For JPY/PLN and CHF/PLN, a high value of the Hurst exponent indicates long memory in the time series. Only for USD/PLN, we achieve the Hurst exponent closest to 0.5, which implies market efficiency. The research results obtained based on the UIP hypothesis and fractal analysis are consistent. The study reveals that the market efficiency hypothesis holds only for the most tradable Polish zloty currency pair, i.e., USD/PLN.
Keywords: 330; efficient market hypothesis; foreign exchange market; fractal analysis; Hurst exponent; uncovered interest parity